Population variation in thermal growth responses of juvenile Atlantic cod (Gadus morhua L.) - Harrald, M.; Neat, F.C.; Wright, P.J.; Fryer, R.J.; Huntingford, F.A. (Environmental Biology of Fishes, 2010)
Controlled environment experiments were carried out to investigate thermal influences and population differences on growth of wild-caught juvenile Atlantic cod Gadus morhua L. from two regions of differing thermal regime off Scotland; the Clyde Sea on the west coast and St Andrews Bay on the east coast. Cod from the Clyde demonstrated significantly higher growth rates than cod from St Andrews. In both populations the growth rate was greater at 12A degrees C than at 8A degrees C. These population and temperature effects act to reinforce one another and it could therefore be predicted that the growth differences between the two areas in the wild should be even more pronounced. The results are consistent with the suggestion that cod may be locally adapted to their thermal environment